Northern Pike of North America: population genomics and sex determination - Johnson, Hollie (2019)
Northern Pike (Esox lucius) is an economically and ecologically valuable species with a circumpolar distribution across the Northern Hemisphere. Northern Pike have been shown to have low levels of genetic variation despite their great capacity to colonize new environments. Here, high-resolution resequencing data from 47 Northern Pike from across North America was used for SNP discovery and population analysis. Our analysis reveals an extraordinary lack of genetic variation among Northern Pike with observed heterozygosity (Ho) of just 0.0835. Our analyses suggest that two major groups of Northern Pike exist in North America that are separated by the North American Continental Divide. Genetic variation associated with the stratification of these two groups resides across the genome particularly in gene regions with multiple copy number variants and functions related to immunity, tissue permeability, and development. Northern Pike from Alaska and the Yukon River harbour about two times more heterozygosity than Northern Pike east of the Continental Divide with an average of one heterozygous SNP every 6,250 bases. Populations east of the Continental Divide possess a remarkable level of genetic homogenization with an average of just one heterozygous SNP every 16,500 bases. For comparison, an average of one heterozygous SNP per 309 bases was reported in herring (Martinez Barrio et al., 2016), one per 500 in Atlantic cod (Star et al., 2011), and one per 750 bases in Coho and chinook salmon (Koop, 2018). This is at least 5 – 10 fold less variation than is seen in humans (the 1000 Genomes Project Consortium, 2015). We observed a recently described master sex-determining gene, amhby, in three western North American populations but not in populations east of the Continental Divide. We could not resolve any signals indicating a genetic sex determination system was present in populations from southern Manitoba or the St. Lawrence River. This may indicate that environmental sex determination is at play in these populations. We ...